1980
DOI: 10.1007/bf00232149
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic polyploidization of mouse heart myocytes during the first postnatal week

Abstract: Polyploidization of myocytes in the cardiac ventricle of mice occurs predominantly during the first week of the postnatal life. Using isolated cells it was shown that about 70% of the cardiomyocytes become binuclear at this time (2c x 2), while 10% are mononuclear but contain 4c of DNA, where c was the haploid level of DNA. About 2% of the cell population were reprsented by 4c x 2 or 8c cells. Cytophotometry of Feulgen-stained DNA in 14C-thymidine-labeled nuclei has shown that the cells that enter the mitotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…Notably, features reminiscent of MC have been observed during normal development. Similar sequence of polyploidization events have been described during the development of trophoblast, 125 and of heart myocytes during the first postnatal week, 126 and during reproduction of gland cells and neurons. 127 These observations suggest that MC cannot be considered a simple dysregulation process activated in response to DNA damage but rather represents an example of a programmed event.…”
Section: Discussionsupporting
confidence: 65%
“…Notably, features reminiscent of MC have been observed during normal development. Similar sequence of polyploidization events have been described during the development of trophoblast, 125 and of heart myocytes during the first postnatal week, 126 and during reproduction of gland cells and neurons. 127 These observations suggest that MC cannot be considered a simple dysregulation process activated in response to DNA damage but rather represents an example of a programmed event.…”
Section: Discussionsupporting
confidence: 65%
“…A striking example of this possibility is the progressive accumulation of myofibrils and intermediate filaments in proliferating cardiomyocytes, ending with abortive cytokinesis and accumulation of binucleated cells during the early postnatal period of heart development. 50,51 Therefore, it is conceivable that specific mechanisms may have evolved to cope with the modifications of cytoskeleton that could inhibit cytokinesis in some differentiating cell types. The case of CIT-K is a so far a unique example of how cytokinesis of specific cells can be affected by the lack of a particular protein.…”
Section: Discussionmentioning
confidence: 99%
“…lc, Table 2). Brodsky et al (1980) showed that cells in the mouse myocardium were mostly binucleate and about 10% of the nuclei were polyploid, although in some cases the frequency of polyploid nuclei "Tissues from mice of various crosses as indicated in the text. 63:1 is ethanol: acetic acid (3:1 v/v) fixative, and PFA is 4% paraformaldehyde.…”
Section: Identification Of Polyploid Nuclei In Different Tissuesmentioning
confidence: 99%